2005
DOI: 10.1056/nejmsa043194
|View full text |Cite
|
Sign up to set email alerts
|

Domestic Returns from Investment in the Control of Tuberculosis in Other Countries

Abstract: U.S.-funded efforts to expand the DOTS program in Mexico, Haiti, and the Dominican Republic could reduce tuberculosis-related morbidity and mortality among migrants to the United States, producing net cost savings for the United States.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
102
0
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(105 citation statements)
references
References 27 publications
2
102
0
1
Order By: Relevance
“…29 Because Australia, France, New Zealand and the United States have very similar practices to Canada in terms of screening for TB in new immigrants, lessons learned from this study could have important policy implications for other major immigrantreceiving countries. 30,31 …”
Section: Resultsmentioning
confidence: 88%
“…29 Because Australia, France, New Zealand and the United States have very similar practices to Canada in terms of screening for TB in new immigrants, lessons learned from this study could have important policy implications for other major immigrantreceiving countries. 30,31 …”
Section: Resultsmentioning
confidence: 88%
“…For example, a comparison of 3 strategies for the control of TB among migrants to the USA concluded that government's underwriting of the expansion of the DOTS strategy in Mexico, the Dominican Republic and Haiti was the most effective long-term approach to reducing TB-related morbidity and mortality among migrants from those countries and would produce net savings in the USA [48]. These projected domestic benefits should encourage the governments of developed countries to provide substantial and sustained funding for the control of TB abroad.…”
Section: Resultsmentioning
confidence: 99%
“…For low-incidence countries, such as the United States, investing in global TB control is a cost-effective strategy for reducing TB, domestically and globally (30,31).…”
Section: Discussionmentioning
confidence: 99%